1989
DOI: 10.1002/aic.690350407
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and structural heterogeneity; Benzene adsorption on silicalite

Abstract: Adsorption equilibria have been gravimetrically measured at 10, 20, 30, 50, and 70°C for benzene on pure crystalline silicalite. Isotherms change from type I to type IV with decreasing temperature, indicating heterogeneous behavior. The transition temperature is determined to be 38 t 1 "C by isobaric experiments. Silicalite is energetically homogeneous since there are no cations present. The observed structural heterogeneity is due to the comparable sizes of benzene molecules and the silicalite pore system. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 9 publications
2
41
0
Order By: Relevance
“…Fig. −1 , which is consistent with previously reported data (Flanigen et al, 1978;Wu et al, 1983;Guo et al, 1989). Table 1).…”
Section: Resultssupporting
confidence: 93%
“…Fig. −1 , which is consistent with previously reported data (Flanigen et al, 1978;Wu et al, 1983;Guo et al, 1989). Table 1).…”
Section: Resultssupporting
confidence: 93%
“…for both (Wu et al, 1983; their intersections. Unfortunately, statistically rigor Thamm, 1987a, b;Guo et al, 1989;.…”
Section: Introductionmentioning
confidence: 99%
“…To see the limitation of this assumption, let us consider the transition which is observed in the adsorption of benzene or xylene isomers in silicalite. [209][210][211] Olson et al observed a step in the adsorption isotherm for p-xylene at 70°C, a plateau at a loading of four molecules per unit cell with saturation at six molecules per unit cell (see Figure 22). Van Koningsveld showed that at four molecules per unit cell a structural transition of the zeolite framework from the ortho to the para structure occurs.…”
Section: Flexible Latticementioning
confidence: 99%